Does personality drive price bubbles?. Issue 3 (27th June 2019) - Oehler, Andreas; Wedlich, Florian; Wendt, Stefan; Horn, Matthias
Abstract : Purpose: The purpose of this study is to analyze whether differences in market-wide levels of investor personality influence experimental asset market outcomes in terms of limit orders, price levels and price bubbles. Design/methodology/approach: Investor personality is determined by a questionnaire. These data are combined with data from 17 experimental asset markets. Two approaches are used to estimate market-wide levels of investor personality. First, the market-wide average of each personality trait is determined; second, the percentage of individuals with comparable personality in a market is computed. Overall, 364 undergraduate business students participated in the questionnaire and the experimental asset markets. Findings: Limits and transaction prices are higher in markets with higher mean values in participants' extraversion and openness to experience and lower mean values in participants' agreeableness and neuroticism. In markets with lower mean values of subjects' openness to experiences more overpriced transactions are observed. In markets with a higher proportion of extraverted subjects and a lower proportion of neurotic subjects higher limits and transaction prices are observed. Bubble phases last longer in markets with a higher proportion of extraverted and a lower proportion of neurotic subjects. Originality/value: Overall, the findings suggest that market-wide personality levels influence market outcomes. As a consequence, market-wide levels of personality help to explain prices in auctions with limited number of participants. Additionally, studies that analyze the influence of subjects' characteristics, including risk aversion, emotional states or overconfidence, on market outcomes should also consider personality traits as potential underlying factor.